2019
DOI: 10.1387/ijdb.190049rp
|View full text |Cite
|
Sign up to set email alerts
|

Expression of primary cilia-related genes in developing mouse gonads

Abstract: Mechanisms governing differentiation of the bipotential gonad into the testes or ovaries are complex and still vague. The primary cilium is an organelle involved in cell signaling, which controls the development of many organs, but the role of primary cilium in the sex determination and sexual differentiation of gonads is com-pletely unknown. Here we studied the expression of genes involved in primary cilium formation and function-ing in fetal mouse gonads, before, during and after sexual differentiation. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Primary cilium was identified as a key coordinator of signaling during organogenesis, and it had been shown that the primary cilium participated in receiving signals from Notch, PDGFRα, FGF, Wnt, and Hedgehog pathways (Wainwright et al, 2014). Primary cilia-related genes are present in different cell types of gonads and may be important for the differentiation of gonad cells and sex differentiation of gonads in mammals (Piprek et al, 2019). However, the role of primary cilium in the sex determination and gonadal differentiation in fish is completely unknown.…”
Section: M6a Profiles Of the Flounder Gonadsmentioning
confidence: 99%
“…Primary cilium was identified as a key coordinator of signaling during organogenesis, and it had been shown that the primary cilium participated in receiving signals from Notch, PDGFRα, FGF, Wnt, and Hedgehog pathways (Wainwright et al, 2014). Primary cilia-related genes are present in different cell types of gonads and may be important for the differentiation of gonad cells and sex differentiation of gonads in mammals (Piprek et al, 2019). However, the role of primary cilium in the sex determination and gonadal differentiation in fish is completely unknown.…”
Section: M6a Profiles Of the Flounder Gonadsmentioning
confidence: 99%